2006
DOI: 10.1248/jhs.52.221
|View full text |Cite
|
Sign up to set email alerts
|

Malathion Residue in Wheat Kernels is Degraded by Thion Organophosphorus Pesticide-Specific Carboxylesterase

Abstract: We earlier reported that malathion residue in wheat kernels is enzymatically eliminated by adding water to swell the sample as pretreatment in the official method set forth in the Food Sanitation Law of Japan. We examined the activities of monooxygenase, organophosphorus hydrolase, methyltransferase, and carboxylesterase as possible malathion-degradable enzymes in wheat kernels. GC/MS analysis resulted in no activity of monooxygenase in wheat kernels, because malaoxon was not produced in the reaction mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This is corresponding to the possibility as previously mentioned that malathion is degraded by carboxylesterase in wheat supernatant because the pesticide competitively inhibits against carboxylesterase activity in the supernatant. 17) Therefore, the present results strongly support the possibility.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is corresponding to the possibility as previously mentioned that malathion is degraded by carboxylesterase in wheat supernatant because the pesticide competitively inhibits against carboxylesterase activity in the supernatant. 17) Therefore, the present results strongly support the possibility.…”
Section: Discussionsupporting
confidence: 83%
“…10) However, thiomalic acid and its ethyl esters were not covered as targets in this study, because there was no production of these sulfhydryl compounds from malathion added to wheat supernatant in our previous report. 17) Some organophosphorus hydrolase also produces diethyl malate by hydrolysis of site C. 11) Hydrolysis of site D by carboxylesterase leads to malathion monocarboxylic acid and malathion dicarboxylic acid. We previously demonstrated that malathion could be a substrate of carboxylesterase, since the pesticide competitively inhibited the activity with p-nitrophenyl acetate as the typical substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7) Additionally, the supernatant of this wheat kernel homogenate did not decompose only malathion but other thion organophosphorus pesticides with carboxylester and p-nitrophenyl acetate as a typical substrate for carboxylesterase (3.1.1.1, CE). 8) Since the enzymatic hydrolysis of p-nitrophenyl acetate in the supernatant was inhibited by addition of malathion, the involvement of CE was suspected to cause the malathion degradation in the supernatant. 8) Malathion α-monocarboxylic acid and malathion β-monocarboxylic acid were identified as degradation products of malathion in the supernatant.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphorus pesticides have the advantages of being economic, effective, and convenient, and they are widely used in prevention and control of plant diseases and pests of agriculture [22,23]. Some kinds of the non-durable organophosphorus pesticides also have a longer survival period in certain environmental conditions and would accumulate in the animal body [24].…”
mentioning
confidence: 99%